A proposal for assessing the uncertainty in the measurement of mean nanoparticle diameter with electron microscopy. (1st April 2021) - Lira, I
Abstract: Of paramount importance in the field of nanotechnology is the ability to measure reliably the properties of nanomaterials, especially their size. In general, just an estimate of size is not sufficient: a quantitative indication of the estimate's quality in the form of an assessment of its uncertainty is necessary as well. For example, standard ISO/IEC 17025:2017 (general requirements for the competence of testing and calibration laboratories) stipulates that appropriate methods and procedures shall be used for laboratory activities and for the analysis of data, including the identification and quantification of all contributions to the measurement uncertainties. In order to facilitate compliance with requirements such as these, a procedure is proposed for assessing the uncertainty in the evaluation of the mean area-equivalent diameter of a nanoparticle population by scanning electron microscopy. We take as reference the general approach proposed in the guide to the expression of uncertainty in measurement, which is globally seen as the de facto standard for the evaluation of measurement uncertainty, and as such, it is normally required for accreditation. Thus, the proposed approach, primarily intended for guidance, will hopefully be found practical, understandable and useful. Ideally, it should be validated, and perhaps improved, through international intercomparison exercises.